Working women and labour market inequality. Research project for the Wilfried Martens Centre for European Studies: Final report - July 2018 - Ronald Bachmann; Peggy Bechara; Merve Cim; Anica Kramer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
This report provides an overview of the gender gap in labour market participation across EU countries, its determinants, as well as policies aimed at improving gender equality in the labour market. In doing so, we explore in detail four factors, i.e. education, taxes, childcare provision, and cultural and historic norms, focussing on four case study countries which represent different regions and feature diverse institutional characteristics. Against this background, the report proposes key actions that are likely to reduce the gender gap in labour market participation across the European Union. [...]
Keywords: 330